2020
DOI: 10.1002/ceat.201900620
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Decentralized Process Control for Reactive Dividing‐Wall Columns

Abstract: The reactive dividing-wall column (RDWC) presents a highly integrated process that enables significant reductions in investment costs and energy consumption. However, the high degree of integration of this apparatus causes numerous interactions between kinetics, vapor-liquid equilibrium, and mass transfer. To ensure a reliable operation of the RDWC, suitable control schemes need to be developed and experimentally validated. A decentralized control scheme for the RDWC is presented and for the first time experim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Due to the small internal diameters of the column, the heat transfer between the two sides of the partition can be ignored and so the role of the partition is realized by two parallel glass columns, known as the Petlyuk column configuration, which is thermodynamically equivalent to the RDWC. 44 The public rectifying and stripping sections are 0.3 m high and 0.4 m high, respectively, filled with a 3 × 3 mm 2 θ ring. The four sections are connected with two Y-shaped glass tubes, and one of them above the dividing section is installed with a funnel controlled by an electromagnetic relay to realize the liquid split.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the small internal diameters of the column, the heat transfer between the two sides of the partition can be ignored and so the role of the partition is realized by two parallel glass columns, known as the Petlyuk column configuration, which is thermodynamically equivalent to the RDWC. 44 The public rectifying and stripping sections are 0.3 m high and 0.4 m high, respectively, filled with a 3 × 3 mm 2 θ ring. The four sections are connected with two Y-shaped glass tubes, and one of them above the dividing section is installed with a funnel controlled by an electromagnetic relay to realize the liquid split.…”
Section: Methodsmentioning
confidence: 99%
“…The SCPI developed by our group is made of tin foil and a steel wire mesh assembled into a semicylindrical small box filled with catalysts, as displayed in Figure . Due to the small internal diameters of the column, the heat transfer between the two sides of the partition can be ignored and so the role of the partition is realized by two parallel glass columns, known as the Petlyuk column configuration, which is thermodynamically equivalent to the RDWC . The public rectifying and stripping sections are 0.3 m high and 0.4 m high, respectively, filled with a 3 × 3 mm 2 θ ring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited steady state and dynamic simulation literature has shown the technology to be feasible in simulation, presenting between 15 and 75% energy savings, depending on the test system . Additionally, experimental studies have been performed, including the validation of a steady state and dynamic model. Despite these studies, RDWCs have yet to be commercialized, with no publicly disclosed RDWCs being reported. The likely cause for this absence is the limited amount of literature on the subject.…”
Section: Introductionmentioning
confidence: 99%